Decadal Analysis of ESBL-Escherichia coli Antibiotic Resistance Patterns in Urine Samples from Nepal: A Systematic Review and Meta-Analysis - Chhetri, Bibek Rana; Thapa, Rajat; Banjara, Megha Raj (Journal of Nepal Health Research Council, 2024)
Background: This systematic review aimed to determine the antimicrobial resistance pattern of the extended-spectrum ?-lactamases producing Escherichia coli (ESBL-EC) in urine samples in Nepal. Methods: Systematic literature review was conducted to locate all articles reporting ESBL-EC in urine samples published between January 2012 to December 2022. The Egger’s weighted regression analysis was done to assess the publication bias. A random-effects model was used to calculate the pooled prevalence and corresponding 95% confidence interval due to significant between-study heterogeneity. The strength of correlation between multidrug resistance and ESBL production in E.coli strains was determined using Pearson’s correlation coefficient. The data were analyzed using R-language 4.2.2. software. Results: The combined prevalence of E.coli in urine samples was found to be 14 % (95% CI, 11-18), while the overall pooled prevalence of ESBL E.coli and MDR E.coli were 30% (95% CI, 20-42) and 70% (95% CI, 38-90) respectively. A strong positive correlation of 0.99 (95% CI, 0.89-1.0) was found between ESBL production and MDR among E.coli isolates. Imipenem was the drug of choice against ESBL-E.coli in urine specimens. Conclusions: Our analyses showed the overall ESBL-EC and MDR-EC burden in Nepal is considerably high. Likewise, the study also infers an increasing trend of antibiotic resistance pattern of ESBL-EC in urine samples. Keywords: ESBL-E.coli; multi-drug resistance; Nepal; urine.